2011
DOI: 10.1038/ijo.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of food consumption frequencies derived from the Children's Eating Habits Questionnaire used in the IDEFICS study

Abstract: Objective: To investigate the reproducibility of food consumption frequencies derived from the food frequency section of the Children's Eating Habits Questionnaire (CEHQ-FFQ) that was developed and used in the IDEFICS (Identification and prevention of dietary-and lifestyle-induced health effects in children and infants) project to assess food habits in 2-to 9-year-old European children. Design and methods: From a subsample of 258 children who participated in the IDEFICS baseline examination, parental questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 20 publications
6
158
1
1
Order By: Relevance
“…For two tools there were two articles reporting on each (12)(13)(14)(15) , and another article reported on two other tools (16) . Only two of the tools assessed dairy intake, ten assessed Ca intake and five assessed both.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For two tools there were two articles reporting on each (12)(13)(14)(15) , and another article reported on two other tools (16) . Only two of the tools assessed dairy intake, ten assessed Ca intake and five assessed both.…”
Section: Resultsmentioning
confidence: 99%
“…The more comprehensive results of the study by Veerecken and Maes assessing four dairy items in two age groups demonstrated only moderate repeatability for most of the items with the younger age group tending to perform better than the older group (22) . Similarly, the five dairy items in the Child Eating Habits Questionnaire assessed by Lanfer et al also showed moderate repeatability (15) . Huybrechts et al reported a weighted k value of 0?60 representing only 'good' agreement for their tool but a high correlation (0?80), a non-significant mean difference of only 24 mg, and 57 % correctly classified and no gross misclassification (25) .…”
Section: Tool Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Because there is no corresponding index for European children nor common European guidelines on which to base one, the YHEI, although based on U.S. dietary guidelines, is the best available instrument for generating comparable data among the eight survey countries and drawing conclusions on the relative healthiness of a diet. This index, which measures food consumption and food-related behavioural patterns, is based on food consumption frequencies, which are collected in the IDEFICS survey using the Children's Eating Habits Questionnaire (CEHQ) (Lanfer et al, 2011 Table 1 about here…”
Section: Maternal Employment Diet and Physical Activitymentioning
confidence: 99%
“…This supplement contains many studies carried out to ensure the quality and rigour of measures included in the IDEFICS study. This measurement rigour has been applied to diet 8,9 and physical activity, [10][11][12] as well as to measurement of social and biological determinants [13][14][15] and health consequences. [16][17][18][19][20] Furthermore, the detailed description of both the strengths and limitations with regard to measurement selection and development is an important resource for dissemination, given its potential for shaping future studies.…”
mentioning
confidence: 99%